MoS2 nanostructures as transparent material: Optical transmittance measurements - Sachidanand P.S.; Sreelal M.M.; Reshmi S.; Viswan G.; Mohan M.; Gautam S.K.; Singh R.K.; Bhattacharjee K. (My University, 2025)
Optical transmittance measurements of MoS2 nanostructures with varying film thickness are reported here. Optical transmittance value of the films containing assorted MoS2 nanostructures (revealed by SEM studies) was obtained from optical microscope images taken under white light with 100× magnification and also from the images acquired under an ordinary lens-laser combination. The relationship between the light exposed on the sample and the pixel intensities of the images are being exploited to establish a correspondence between average pixel intensity and the transmittance obtained by numerical coding. Our measurements show a transmittance variation in the range of 0.92-0.68 with sample thickness. © 2018 Elsevier Ltd.